A Research Note on using Mortality Statistics in Tort Claims - Chan, Felix W. H.; Chan, Wai-sum (European Scientific Journal, ESJ, 2020)
Personal injury insurers constantly need to model the future mortality experience in the process of handling tort claims. Various stochastic mortality modelling techniques are deployed so that lawyers and actuaries specialised in this field of civil litigation can effectively perform the procedures related to dispute resolution and assessment of compensation. In this project, how lump sum awards are judicially determined in Hong Kong is examined. The impact of future mortality rates is discussed in the context of future medical expenses and loss of future earning as a result of discounting the future pecuniary values into a single present-day amount. The time value of money affected by inflation and the claimant’s mortality are among the key factors to be calibrated in the present study. The work described in this paper was fully supported by a grant from the Research Grants Council of the Hong Kong Special Administrative Region, China (Project No. HKU 17636316).